The role of genetic, autoimmune, infective and hormonal factors in pathogenesis of lichen sclerosus – review of the literature - Cegielska, Agnieszka; Imko-Walczuk, Beata; Jaśkiewicz, Janusz; Placek, Waldemar (Dermatology Review/Przegląd Dermatologiczny, 2011)
Lichen sclerosus (LS) is a chronic inflammatory disease with a characteristic clinical appearance and specific histopathology. Clinically is characterized by plaques of ivory white atrophic lesions licalized, chiefly on genitals, and also in extragenital localisation. Both males and females at any age are affected. The aetiology of LS remains unclear. In the literature, the hypothesis of possible role of genetic, autoimmune, infectious and hormonal factors are found. Oxidative stress may also play additional role. Understanding of lichen sclerosus pathogenesis may improve its therapy and allow to avoid its complications.